2019
DOI: 10.4103/jomfp.jomfp_191_18
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclooxygenase 2 in oral submucous fibrosis: An immunohistochemical pilot study

Abstract: Introduction: Oral submucous fibrosis (OSF) is associated with inflammatory changes in at least some stages of the disease. Prostaglandin is one of the main inflammatory mediators and its production is controlled by various enzymes such as cyclooxygenase (COX). The genetic and pharmacological data strongly indicate that COX-2 should be investigated as a potential target for the prevention and treatment of OSF. Methodology: The study group comprised histologically confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…The immunoexpression of COX 2 in the present study was significantly increased in the OSMF group, when compared with controls, with none of the normal patients showing positivity to COX 2, the results of which were in correlation with a similar study. [ 17 ] Similar correlation with the present study was observed in a study done by Tsai et al ,[ 35 ] in which COX 2 expression was upregulated in OSMF specimens compared with normal buccal mucosa, with strong immunostaining for COX-2 being detected in epithelial cells, fibroblasts, and inflammatory cells. Statistically significant expression of COX 2 was observed on comparison with normal, OSMF, and OSCC, with increased expression of advanced stage of OSMF in a study done by Singh et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The immunoexpression of COX 2 in the present study was significantly increased in the OSMF group, when compared with controls, with none of the normal patients showing positivity to COX 2, the results of which were in correlation with a similar study. [ 17 ] Similar correlation with the present study was observed in a study done by Tsai et al ,[ 35 ] in which COX 2 expression was upregulated in OSMF specimens compared with normal buccal mucosa, with strong immunostaining for COX-2 being detected in epithelial cells, fibroblasts, and inflammatory cells. Statistically significant expression of COX 2 was observed on comparison with normal, OSMF, and OSCC, with increased expression of advanced stage of OSMF in a study done by Singh et al .…”
Section: Discussionsupporting
confidence: 93%
“…In an attempt to find the association of dysplasia connected with OSMF with COX 2 expression, it was found to be statistically insignificant, probably attributed to the lower sample size. [ 17 ] However, in the present study on comparison with normal, atrophic, mild, and moderately dysplastic epithelium, statistically significant difference was noted with the expression of COX 2. Evaluation of clinical and histopathological parameters, using univariate and multivariate analyses, showed that COX 2 expression along with nature of the epithelium and vascularity together as a model would help in identification of disease progression in OSMF.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…α‐SMA, 23 podoplanin, 41 cyclooxygenase‐2 (COX2), 42 α‐enolase, 43 p53, 24 p63, 44‐46 ΔNp63, 44 p16, 24 Ki67, 23,27 cytokeratin (CK‐5/6), 44 VEGF, 47 CD105, 23,45,47 vimentin, 48 PCNA, 49 caspase‐3, 50 SOX2, Bmi1, 27 and cytoplasmic expression of E‐cadherin and β‐catenin 49 were upregulated in OSF with dysplasia compared with OSF without dysplasia and normal subjects. Loss of membranous E‐cadherin and β‐catenin was evident in OSF with moderate and severe dysplasia 45–47 …”
Section: Discussionmentioning
confidence: 99%